Effectiveness educational video of Breast Self Examination (BSE) on knowledge of young women - Damayanti, Siti; Apriani, Fitri; Nasution, Nurromsyah; Miswarni, Miswarni (Science Midwifery, 2024)
Background: BSE examinations are conducted as early as feasible while women are still young, that is, when they are productive and between the ages of 13 and 49, they will also be very successful. Women in this age group are more likely to get cancer or breast tumors. The issue lies in women's lack of knowledge about the risks associated with BSE practice, which ranges from 25% to 30%. Adolescents' awareness can be raised more easily when education through video media stimulates their auditory and visual senses. The study's objective was to ascertain how young women's knowledge was impacted by the instructional film on breast self-examination (BSE). Method: A quasi-experimental study design without control is employed, consisting of pre- and post-test phases. The study, which involved 94 teenage female students, was carried out at MTSN 01 West Aceh from April 29 to May 21, 2024. Purposive sampling with inclusion criteria was the sample strategy used in this study. The study's findings demonstrate a substantial relationship between video-based BSE education and young women's BSE knowledge, with a p-value of 0.000<0.05 for the Wilcoxon test results. Conclusion: The degree of knowledge of female students is significantly influenced by BSE instruction through video. Increasing the level of knowledge among female students.